Analisis Pengaruh Patient-Perceived Hospital Service Quality terhadap Customer Satisfaction dan Behavioral Intention Pelayanan Rawat Inap - Arlina, Launa Inayati; Yuanasika, Dwiky; Qomaruddin, Mochammad Bagus; Chalidyanto, Djazuly (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2026)
The Bed Occupancy Rate (BOR) of inpatient rooms at Mitra Sehat Mandiri Hospital Sidoarjo during 2019-2023 has not reached the ideal standard. The BOR values were 22%, 28%, 37%, 25%, and 20%, with an average of 26.4%, remaining below the ideal range of 60-85%. One of the most influential factors contributing to the low BOR is suboptimal service quality. This study aims to analyze the relationship between Patient-Perceived Hospital Service Quality, customer satisfaction , and behavioral intention among inpatients at Mitra Sehat Mandiri Hospital Sidoarjo. This study employed a quantitative method with an analytical approach and a cross-sectional design. The population included all inpatients, with a sample of 97 respondents determined using the Lemeshow formula. Multiple linear regression was conducted to examine the influence of variables. The results showed that the dimensions of Clinical Care Process, Relationship, and Administrative Procedures contribute significantly to customer satisfaction, with p-values of 0.006, 0.026, and 0.032, respectively. In addition, Trustworthiness, Clinical Care Process, and Administrative Procedures also significantly affected patients’ behavioral intention with a p-value < α (0.05). Furthermore, customer satisfaction has a significant effect on the behavioral intention of inpatients, as evidenced by a p-value < α (0.05). These findings indicate that improving service quality in various crucial aspects can encourage customer satisfaction and strengthen positive behavioral intentions in hospital services. Overall, the study concludes that improvements in key aspects of Patient-Perceived Hospital Service Quality directly enhance customer satisfaction, which in turn strengthens positive behavioral intention at Mitra Sehat Mandiri Hospital Sidoarjo.